Effect of seed rate on biomass production of Dhaincha (Sesbania aculeata) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
A field experiment was conducted at the Agronomy field, Patuakhali Science and Technology University (PSTU), Patuakhali during the period of May 2013 to August 2013. The experiment was conducted to find out the effect of seed rate on nodulation of dhaincha (Sesbania aculeata) under non-saline agro-ecosystem. The experiment comprised of seven different seed rates viz. 30, 35, 40, 45, 50, 55 and 60 kg ha-1. The experiment was laid out in randomized complete block design with three replications. The seed rates had significant influence on different parameters of dhaincha plant. It was found that (30 kg ha-1) recorded the tallest plant (4.11 m) followed by (45 kg ha-1) while (60 kg ha-1) gave the smallest plant (3.66 m). Recorded maximum plant diameter was (0.92 cm) at harvest while the lowest plant diameter was obtained from (55 kg seed ha-1) (0.79).The highest plant population (336.0) was found in (60 kg ha-1) while (30 kg ha-1) showed the lower plant population (114.0). The maximum number of branches (23.93 plant-1) at harvest while (60 kg ha-1) produced the lowest number of branches plant–1 (7.93 plant-1). It was recorded that (60 kg ha-1) produced the highest fresh weight m-2 (4.10 kg) and was statistically different from other treatments. On the other hand, (30 kg ha-1) produced significantly the lowest fresh weight of plants m-2 (1.93 kg) which was also statistically different from other treatments. The higher below ground biomass production m-2 (1.00 kg) was found in ( 30 kg ha-1 ) followed by ( 35 kg ha-1 ), ( 40 kg ha-1 ) and ( 45 kg ha-1 )while ( 50 kg ha-1 ) observed the lower below ground biomass production m-2(0.19 kg) at (60 kg ha-1). Production of pods branch-1 was maximum (22.00) at (30 kg ha-1) followed by (35 kg ha-1) while the lowest number of pods branch-1 (17.07) at (60 kg ha-1). It was found that (30 kg ha-1) produced the maximum number of seeds pod–1 (32.73) which was significantly different from other treatments. On the other hand, (60 kg ha-1) recorded the significantly minimum number of seeds pod–1 (25.40) which was also statistically similar with (60 kg ha-1).Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 316-322